Adipogenic/lipogenic gene expression and fatty acid composition in chuck, loin, and round muscles in response to grain feeding of Yanbian Yellow cattle. (21st June 2018) - Li, Xiang Z; Yan, C G; Gao, Qi S; Yan, Y; Choi, Seong H; Smith, Stephen B
Abstract: We hypothesized that gene expression and fatty acid composition would differ among different muscle depots and over time on a grain-based finishing diet. Additionally, we hypothesized that the concentration of SFA would decrease and the concentration of MUFA would increase proportionately with increases in percent intramuscular lipid (%IML ). Ten Yanbian Yellow cattle steers (approximately 8 mo of age) were fed a corn-based diet in which the proportion of corn in the ration was increased at 4-mo intervals. Muscle samples were taken by biopsy from the chuck (trapezius), loin (longissimus dorsi), and round (biceps femoris) muscles at 12, 16, 20, 24, and 28 mo of age. The %IML increased from 12 to 28 mo of age, especially between 24 and 28 mo of age, with loin > round > chuck (age × muscle interaction P < 0.001). The percentage (g/100 g total fatty acids) of oleic acid (18:1n-9), linoleic acid (18:2n-6), and α-linolenic acid (18:3n-3), and the MUFA:SFA ratio increased with age, whereas palmitic (16:0) and stearic acid (18:0) decreased with age in all muscles (age effect P < 0.001). The expression of sterol regulatory element binding protein ( SREBP1 ), adipose tissue fatty acid- binding protein ( FABP4 ), stearoyl-CoA desaturase ( SCD ), acetyl-CoA carboxylase ( ACC1 ), and lipoprotein lipase ( LPL ) increased, whereas the expression of peroxisome proliferator-activated receptor gamma ( PPARγ ) and fatty acid synthase ( FASN ) decreased with age. Expression of PPARγ, FABP4, SREBP1, SCD, FASN, ACC1, and LPL was greater in the loin than in the chuck or round (age × muscle interaction P < 0.001), although the MUFA:SFA ratio was greater in the chuck than in the loin or round (muscle effect P < 0.001). In conclusion, adipogenic gene expression was greater in the loin than in the chuck or round muscles, consistent with the greater %IML of the loin. However, the greater SCD gene expression in the loin did not result in a greater amount of MUFA in the loin, relative to the chuck and round.